2006
DOI: 10.1107/s1744309106009274
|View full text |Cite
|
Sign up to set email alerts
|

Expression, purification and crystallization of the SARS-CoVmacrodomain

Abstract: Macro domains or X domains are found as modules of multidomain proteins, but can also constitute a protein on their own. Recently, biochemical and structural studies of cellular macro domains have been performed, showing that they are active as ADP-ribose-1 00 -phosphatases. Macro domains are also present in a number of positive-stranded RNA viruses, but their precise function in viral replication is still unknown. The major human pathogen severe acute respiratory syndrome coronavirus (SARS-CoV) encodes 16 non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…We have determined two novel alphavirus macro domain crystal structures and shown that these domains can bind ADPribose, RNA, and PAR. The crystal structures of the alphavirus macro domains show a high degree of conservation with other available macro domain structures (2,4,10,19,20,27,43). Surprisingly, the macro domain that shows the highest sequence and structural similarity to alphavirus macro domain is that of E. coli and not coronavirus.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…We have determined two novel alphavirus macro domain crystal structures and shown that these domains can bind ADPribose, RNA, and PAR. The crystal structures of the alphavirus macro domains show a high degree of conservation with other available macro domain structures (2,4,10,19,20,27,43). Surprisingly, the macro domain that shows the highest sequence and structural similarity to alphavirus macro domain is that of E. coli and not coronavirus.…”
Section: Discussionmentioning
confidence: 82%
“…The crystal structures of several macro domains have been determined in archaebacteria (Archaeoglobus fulgidus) (2), eubacteria (Escherichia coli and Thermus thermophilus), and eukaryotes (Saccharomyces cerevisiae, Rattus norvegicus, and Homo sapiens) (4,19,20). The crystal structure of the macro domain of the coronavirus responsible for severe acute respi-ratory syndrome (SARS-CoV) has also been determined (10,27,43). The structural conservation between these structures is remarkable and they have been defined as a family in the SCOP database (30).…”
mentioning
confidence: 99%
“…The previously characterized yeast protein Poa1p 7 was produced as control, and the SARS-CoV macro domain was obtained as previously described. 30 The proteins were purified by metal chelate chromatography, in some cases followed by a second puri-fication step ( Fig. 1c; see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…SARS-CoV macro protein was kindly provided by Dr. Bruno Canard (CNRS, Marseille, France). 30 Human macro protein encoding sequences were also cloned to vectors for expression in mammalian cell lines. Two constructs, encoding either the full-length protein or a truncated derivative (macro domain with some flanking amino acids), were made for each protein.…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…CoV macro domain (residues 182 to 355 of SARS-CoV nsp3) was expressed in Escherichia coli after cloning of the corresponding gene region (isolate Frankfurt 1, DDBJ/EMBL/GenBank accession number AY291315) into pDEST14 plasmid (Invitrogen). A detailed report on cloning, expression, and purification is reported elsewhere (21). Mutant forms of this protein were produced by codon mutagenesis of plasmid pDEST14 (Invitrogen) using PCR-based methods as described previously (30).…”
Section: Preparation Of Recombinant Macro Domain Proteins the Recombmentioning
confidence: 99%